An Active Virtual Space Vector Modulation Scheme for Three‐Level Neutral‐Point‐Clamped Converters - Huang, Zhen; Zhang, Shuhao; Wang, Jingyi; Xia, Yonghong (IEEJ transactions on electrical and electronic engineering, 2024)
The performance of neutral‐point‐clamped (NPC) converters is subject to the regulation of neutral point balance. In the literature, researchers have addressed two main modulation methods: the active space vector PWM (SVPWM) technique and the virtual SVPWM (VSVPWM) method. However, those two approaches respectively suffer from reduced DC‐link voltage utilization and poor active regulation capability. To address this, an improved VSVPWM modulation scheme with actively strong voltage regulation capability is proposed in this paper. The fast and precise control of capacitor voltages is achieved by optimizing the synthesis scheme of the virtual vectors. When there is a voltage imbalance, the proposed technique can quickly restore and maintain the capacitor voltage balance till the full DC‐link voltage utilization without affecting the converter output quality. The experimental validation results on the NPC converter have demonstrated the benefits of the proposed active VSVPWM method. © 2024 Institute of Electrical Engineers of Japan and Wiley Periodicals LLC.